The efficacy of curcuminoids in improvement of ulcerative colitis symptoms and patients' self‐reported well‐being: A randomized double‐blind controlled trial. Issue 11 (21st August 2018) - Masoodi, Mohsen; Mahdiabadi, Mohammad Ali; Mokhtare, Marjan; Agah, Sharam; Kashani, Amir Hossein Faghihi; Rezadoost, Amir Mansoor; Sabzikarian, Mohammad; Talebi, Atefeh; Sahebkar, Amirhossein
Abstract: Background: Curcuminoids are polyphenols with documented anti‐inflammatory activity and has been shown to improve the symptoms of several inflammatory diseases. We aimed to evaluate the effectiveness of a nanoformulation of curcuminoids in the treatment of ulcerative colitis. Methods: This randomized double‐blinded controlled trial was conducted on 56 patients aged 18 years or older with the final diagnosis of mild to moderate ulcerative colitis according to the Simple Clinical Colitis Activity Index (SCCAI). The patients were randomly assigned (using a computerized random sampling table) to receive curcuminoids nanomicelles (80 mg, three times daily, orally) plus mesalamine (3 g/24 hours, orally) as the treatment group and placebo plus mesalamine (3 g/24 hours, orally) as the control group for a period of four weeks. The severity of disease was assessed at baseline and at the end of the second and fourth weeks of the treatment according to the SCCAI. Results: The score for urgency of defecation reduced significantly more in case group as compared with control group at four weeks after beginning the treatment. The patients in case group experienced better general condition than the control ones after 4 weeks of treatment. Overall, the mean SCCAI score was significantly lower in the patients received curcuminoids nanomicelles plus mesalamine as compared with the group received placebo plus mesalamine at fourth week after the treatment (1.71 ± 1.84 vs 2.68 ± 2.09, p  = 0.050). Conclusion: Adding curcuminoids nanomicelles to routine treatment of patients with ulcerative colitis is associated with a significant improvement of symptoms, including reduced frequency of urgent defecation, improved patients' self‐reported well‐being and reduced clinical activity of ulcerative colitis. ClinicalTrials. "IRCT2017052634142N1". Abstract : We aimed to evaluate the effectiveness of a nanoformulation of curcumin in the treatment of ulcerative colitis.